Confined synthesis and interlayer coupling of patterned graphene ribbons arrays. (May 2022) - Xiong, Xuyao; Ning, Congcong; Jin, Yan; Li, Dongling; Yang, Qian; Gong, Xiangnan; Cheng, Chao; Pan, Qingjiang; Xu, Yi; Hu, Baoshan
Abstract: To prepare patterned graphene ribbons with fixed directions and positions can promote the applications of graphene in optoelectronic devices. The templated chemical vapor deposition (CVD) approach is promising for the growth of graphene ribbons, however the patterned metal substrate with micro- and nano-scale geometry conventionally experiences the uncontrollable dewetting and deformation. Herein, we proposed a trapezoidal groove-confined strategy to regulate the dewetting mechanism of ribbon-shaped metal film in terms of film thickness, annealing temperature and Ni adhesion layer, and then synthesized pure and N-doped graphene ribbons arrays. Subsequently, we perpendicularly stacked the graphene ribbons and N-doped graphene ribbons to investigate the interlayer coupling interaction with variable temperature Raman spectroscopy, and discovered some novel Raman scattering modes. The findings can deepen our understanding on confined synthesis strategy with respect to interlayer interaction-related attributes of graphene ribbons. Graphical abstract: Image 1